2015
DOI: 10.1111/jce.12695
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long‐Term Outcomes of Catheter Ablation of Atrial Fibrillation Using the Second‐Generation Cryoballoon versus Open‐Irrigated Radiofrequency: A Multicenter Experience

Abstract: Second-Generation Cryoballoon versus RF. Introduction:There are limited comparative data on catheter ablation of atrial fibrillation (CAAF) using the second-generation cryoballoon (CB-2) versus point-by-point radiofrequency (RF). This study examines the acute/long-term CAAF outcomes using these 2 strategies.Methods and Results: In this multicenter, retrospective, nonrandomized analysis, procedural and clinical outcomes of 1,196 patients (76% with paroxysmal AF) undergoing CAAF using CB-2 (n = 773) and openirri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 23 publications
7
109
3
Order By: Relevance
“…In fact, the majority of patients in the RF group received treatment with the first generation device, while for the CB procedure, there were significantly more second generation devices used. Notably, there are early indications that the non-inferiority of CB compared to RF could be maintained for the later generations of catheter ablation systems [13, 15, 30]. However, at present, there are no long-term data available concerning the efficacy of the newer systems.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the majority of patients in the RF group received treatment with the first generation device, while for the CB procedure, there were significantly more second generation devices used. Notably, there are early indications that the non-inferiority of CB compared to RF could be maintained for the later generations of catheter ablation systems [13, 15, 30]. However, at present, there are no long-term data available concerning the efficacy of the newer systems.…”
Section: Discussionmentioning
confidence: 99%
“…During the off period, tissue temperature remains close to target. 49 The cryoballoon and radiofrequency ablation will be compared in the prospective randomized FIRE AND ICE trial, 50 with results expected in 2016. Cryoballoon ablation is also being investigated as first-line therapy in patients with paroxysmal AF in the Cryo-FIRST Trial (NCT01803438).…”
Section: Cryothermal Ablationmentioning
confidence: 99%
“…These study results are consistent with the outcomes reported in other global trials of the effectiveness of cryoballoon. [8][9][10][11][12] Although this study was a PMS, the safety outcome seems not a significant problem with new cryoballoon users.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Most of the studies demonstrated a similar efficacy between cryoablation and irrigated-tip RF ablation for paroxysmal AF. [8][9][10][11][12] In most studies, procedural duration was shorter and fluoroscopic exposure a little longer than with conventional RF ablation with 3D mapping system. Nevertheless, efficacy is not the only issue we need to consider; safety is also paramount before making this ablation technique available to most operators, including less experienced doctors.…”
mentioning
confidence: 99%
See 1 more Smart Citation